Translating Laughter: The Impact of Humor Translation on Readers’ Engagement in Mahfouz’s Zuqāq al-Midaq - Alhomidy, Yassin (International Journal of Linguistics and Translation Studies, 2026)
This study aims to investigate whether the translator of Zuqaq al-Midaq has preserved or modified the intentional humor from Arabic into English. It explores the maxims that have been flouted by the joke teller in the target text (TT) and identifies the most effective microstrategies in rendering intentional humor into the TT. It is a qualitative study that explores the impact of translating humor on readers’ engagement in the novel genre. The theories adopted in this study are Raskin’s (1985) Semantic Script Theory of Humor (SSTH) and Grice’s (1975) Cooperative Principle (CP). The corpus comprises 12 humorous utterances of Naguib Mahfouz’s (1947) Zuqaq al-Midaq and its translation, Midaq Alley, by Trevor le Gassick (1975). The findings of the study demonstrate that the translator has aptly rendered the ST humorous effect to the target reader in most of the selected utterances. Adaptation and oblique translation constitute the most effective microstrategies, whereas condensation and explicitation may render the ST laughter to a certain extent due to cultural nuances. Direct translation may render intentional humor except for culture-specific items. Grice’s quality maxim is the most flouted in translation. The study instigates translation practitioners to explore how translating humor may influence the characterization and plot of the novel genre.